Gain stabilization for radio intensity mapping using a continuous-wave reference signal - Pollak, A; Holler, C; Jones, M; Taylor, A (Oxford University Press, 2019)

(untitled)
Stabilizing the gain of a radio astronomy receiver is of great importance for sensitive radio intensity mapping. In this paper we discuss a stabilization method using a continuous-wave reference signal injected into the signal chain and tracked in a single channel of the spectrometer to correct for the gain variations of the receiver. This method depends on the fact that gain fluctuations of the receiver are strongly correlated across the frequency band, which we can show is the case for our experimental set-up. This method is especially suited for receivers with a digital back-end with high spectral resolution and moderate dynamic range. The sensitivity of the receiver is unaltered except for one lost frequency channel. We present experimental results using a new 4–8.5 GHz receiver with a digital back-end that shows substantial reduction of the 1/f noise and the 1/f knee frequency.